Penerapan Supervisi Klinis dalam Pelaksanaan PPL II Mahasiswa PGSD - Wilson Takaendengan; Bertu Rianto Takaendengan (Pendagogia: Jurnal Pendidikan Dasar, 2021)
The research aims to get an overview of: 1) the benefits of clinical supervision in helping practitioners carry out field experience practices (PPL II); 2) the essence of the application of clinical supervision in solving teaching problems; 3) the contribution of the application of clinical supervision in developing the professional abilities of prospective teacher students. This research was conducted at SD Inpres Kakaskasen 3 Tomohon using a qualitative approach. Data is collected using interview, observation and documentation techniques. The results showed that the application of clinical supervision effectively: 1) can help practioner to improve the quality of teaching in elementary schools; 2) the answer to overcome various problems in the learning process; 3) can help practitioners to develop their professional abilities. The conclusions are that: 1) the application of clinical supervision helps improve the teaching quality; 2) clinical supervision is the answer in overcoming problems in the learning process; 3) through clinical supervision, practitioner are able to develop their professional abilities. As suggestions: 1) the mentoring process from the supervising lecturers, principals and tutors must focus on the needs of practicioner; 2) the mentoring process must be more helpful that the motivation and creativity of students/practitioners can develop properly.